Perspectives of nonalcoholic fatty liver disease research: a personal point of view - Amedeo Lonardo; Stefano Ballestri (Open Exploration Publishing Inc., 2020)
Rational government of patient fluxes from primary care to hepatology clinic is a priority of nonalcoholic fatty liver disease (NAFLD) research. Estimating pre-test probability of disease, risk of fibrosis progression, and exclusion of competing causes of liver disease must be addressed. Here we propose a novel taxonomic classification of NAFLD based on hepatic, pathogenic and systemic features of disease in the individual patient. The variable course of disease in any given patient remains a clinical enigma. Therefore, future studies will have to better characterize the role of genetic polymorphisms, family and personal history, diet, alcohol, physical activity and drugs as modifiers of the course of disease and clues to the early diagnosis of hepatocellular carcinoma. A better understanding of these, together with a taxonomic diagnosis, may prompt a more accurate personalization of care. For example, understanding the putative role of psycho-depression in NAFLD promises to revolutionize disease management in a proportion of cases. Similarly, sex differences in outcome and response to treatment are insufficiently characterized. More studies are awaited regarding those forms of NAFLD which occur secondary to endocrine derangements. The intersections between NAFLD and the lung must better be defined. These include the bi-directional associations of NAFLD and chronic obstructive pulmonary disease and sleep apnoea syndrome, as well as the totally unexplored chapter of NAFLD and coronavirus disease 2019 (COVID-19). Finally, the therapeutic roles of intermittent fasting and anticoagulation must be assessed. In conclusion, over the last 20 years, NAFLD has taught us a lot regarding the pathogenic importance of insulin resistance, the limitations of correcting this in the treatment of NAFLD, the root causes of diabetes and the metabolic syndrome, sex differences in disease and the role of nuclear receptors. However, the overwhelming COVID-19 pandemic is now expected to reset the priorities of public health.